Simulation of flow velocity variations in the Cai Khe Channel during sluice gate operation - Dinh, Van Duy; Nguyen, Hoang Phuc (CTU Journal of Innovation and Sustainable Development, 2025)
The three-dimensional hydraulic model Flow-3D was used to simulate the flow velocity in the Cai Khe channel when operating the gates of the Cai Khe barrier. Primary and secondary data were collected to build, calibrate, and validate the model. The NSE coefficient for calibration and validation cases were 0.74 and 0.61, respectively, indicating the reliability of the model. The case of operating the gate to discharge pollutants and create a unidirectional flow with a water level difference between the field and the river of 1.54 meters was chosen to check for potential erosion. The simulation results showed that at profiles 1 and 2 (located 10 meters and 60 meters from the center of the sluice towards the river, respectively), the average flow velocities were 2.97 m/s and 4.99 m/s, respectively, which are greater than the allowable non-erosive velocity (vx = 0.19 – 0.26 m/s). Therefore, the riverbed needs to be reinforced to prevent erosion when operating the sluice gates.